Soft Lens - Soemarsono Soemarsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
I have presented the use of soft lenses which has a wider range when compared with that of the usual spectacles. There are some complications but we can prevent them by supervising their use.The result of the use of soft lens during three :.ears was presented. No serious complications were met. The soft lens is relatively expensive because the material is imported. Patients desiring contact lenses must exactly know the problems.Key Words: soft lens - contact lens - refraction anomaly - aphakia - erosio corneae